A Study of Mechanical Property of Artificial Frozen Clay under Dynamic Load. (23rd January 2018) - Li, Dongwei; Fan, Juhong
Abstract : To determine the mechanical properties of artificial frozen clay under dynamic load, 81 triaxial shear tests were carried out for artificial frozen clay at different temperatures, amplitudes, frequencies, and precompressions and three kinds of testing conditions. The change laws of the dynamic modulus of elasticity, maximum dynamic shear modulus, dynamic damping ratio, and strain rate were determined. These results can guide future research on the mechanical mechanisms of frozen soil, providing both theoretical and practical significance.